Multi-layer co-extrusion PE stretching wrapping film
By combining a variety of materials and structures in a multi-layer coextruded PE stretched winding film, the performance bottlenecks of the existing winding film in terms of wear resistance, high temperature resistance, chemical resistance and mechanical strength are solved, and higher comprehensive performance and applicability are achieved.
Patent Information
- Application Number
- CN202411849134.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
The existing multi-layer coextruded PE stretched wound film has performance bottlenecks in terms of wear resistance, high temperature resistance, chemical resistance and mechanical strength, and it is difficult to meet the complex and diverse application environment needs.
The multi-layer coextruded PE stretched wrap film is prepared by combining polyethylene, polyhedral oligosilsesquioxane, ethylene-vinyl acetate, binder resin, polypropylene, nanozirconia particles, polyether ether ketone, antistatic agent, slip agent and ultraviolet absorber, to construct a multi-layer structure to improve the performance of the film.
It significantly improves the wear resistance, high temperature resistance, chemical resistance and mechanical strength of the film, and is suitable for applications with high temperature environments and high wear resistance requirements, improving the comprehensive performance and market competitiveness of packaging materials.
Smart Images

Figure CN119636209A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PE wrapping films, and in particular to a multi-layer co-extruded PE stretch wrapping film. Background Art
[0002] With the rapid development of modern industry and logistics, packaging materials play an increasingly important role in ensuring product safety and improving transportation efficiency. As a high-performance packaging material, multi-layer co-extruded PE stretch wrapping film is widely used in the packaging of various products due to its excellent stretchability, wrapping and protection. However, with the increasing complexity and diversification of the application environment, the market's performance requirements for this packaging material are also constantly increasing. In particular, in terms of wear resistance, high temperature resistance, chemical resistance and mechanical strength, the existing multi-layer co-extruded PE stretch wrapping film still has certain performance bottlenecks.
[0003] Although multi-layer co-extruded PE stretch wrapping film has been widely used in the packaging industry, the existing products and technologies still have the following shortcomings:
[0004] Wear resistance and high temperature resistance need to be improved: In high temperature environments or application scenarios that require long-term friction, traditional multi-layer co-extruded PE stretch wrap films are often difficult to maintain stable performance and are prone to problems such as wear or deformation.
[0005] Insufficient chemical resistance: Certain specific application environments require packaging materials to have good chemical resistance to resist the erosion of chemicals such as acids and alkalis. However, the existing multi-layer co-extruded PE stretch wrapping film does not perform well in this regard.
[0006] Mechanical strength needs to be enhanced: With the rapid development of the logistics industry, the requirements for the mechanical strength of packaging materials are getting higher and higher. Traditional multi-layer co-extruded PE stretch wrapping film is prone to breakage or damage when subjected to large tension or impact.
[0007] Therefore, we proposed a multi-layer co-extruded PE stretch wrap film to solve the above problems. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a multi-layer co-extruded PE stretch wrapping film.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] A multi-layer co-extruded PE stretch wrapping film comprises the following components in parts by weight: 50-70 parts of polyethylene, 1-5 parts of polyhedral oligomeric silsesquioxane, 5-15 parts of ethylene-vinyl acetate, 3-10 parts of adhesive resin, 5-15 parts of polypropylene, 1-3 parts of nano zirconium oxide particles, 1-5 parts of polyetheretherketone, 1-3 parts of antistatic agent, 0.5-2 parts of slip agent and 0.5-2 parts of ultraviolet absorber.
[0011] As the preferred technical solution:
[0012] The multi-layer co-extruded PE stretch wrapping film as described above comprises the following components in parts by weight: 53 parts of polyethylene, 4 parts of polyhedral oligomeric silsesquioxane, 8 parts of ethylene-vinyl acetate, 5 parts of adhesive resin, 9 parts of polypropylene, 2 parts of nano zirconium oxide particles, 3 parts of polyetheretherketone, 2 parts of antistatic agent, 0.8 parts of slip agent, and 1.5 parts of ultraviolet absorber.
[0013] In the multi-layer co-extruded PE stretch wrapping film as described above, the molecular weight distribution index of the polyethylene is 3.0-3.5; the polyhedral oligomeric silsesquioxane is an octahedral structure, in which the silicon-oxygen bond is the main connecting bond; the VA content in the ethylene-vinyl acetate is 20-25%; the mass fraction of the polar group in the adhesive resin is 1-3%, the polar group includes carboxyl and hydroxyl, and the adhesive resin is one of rosin resin, terpene resin, phenolic resin, and petroleum resin; the polypropylene is isotactic polypropylene, and its melt flow rate is 2-5g / 10min; the crystal structure of the polyetheretherketone is an orthorhombic system; the particle size of the nano zirconium oxide particles is 50-100nm; the antistatic agent is an ethoxylated amine antistatic agent, the slip agent is erucamide, and the ultraviolet absorber is a benzophenone ultraviolet absorber.
[0014] In the multi-layer co-extruded PE stretch wrap film as described above, the polyethylene is a branched structure PE; the polyhedral oligomeric silsesquioxane has multiple reaction sites, which enables it to connect multiple PE chains to build a more stable network structure.
[0015] In the multi-layer co-extruded PE stretch wrapping film as described above, the polyhedral oligomeric silsesquioxane has a hollow spherical structure; the nano zirconium oxide has a one-dimensional nanostructure, including nanowires and nanorods, forming a reinforcement skeleton in the film, and setting the reinforcement skeleton efficiency index as RSEI, then:
[0016] RSEI=\frac{\ph i\t imesE_{ZrO_2}}{1-\ph i}
[0017] E_{ZrO_2} is the elastic modulus of nano-zirconia; \ph i is the volume fraction of nano-zirconia.
[0018] The second aspect of the present invention provides a method for preparing a multi-layer co-extruded PE stretch wrap film, comprising the following steps:
[0019] S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent;
[0020] S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are on the outermost layer. Multi-layer co-extrusion equipment is used to ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer;
[0021] S3: solidification of the multilayer melt by cooling in a water bath;
[0022] S4: Biaxial stretching, first in the machine direction by increasing the speed of the roller stretching, and then in the transverse direction using a tenter stretching machine, and then using a winder, to obtain a multi-layer co-extruded PE stretch wrap film.
[0023] As the preferred technical solution:
[0024] The method for preparing a multi-layer co-extruded PE stretch wrap film as described above, wherein S1 specifically comprises:
[0025] S11: polyethylene and isotactic polypropylene are selected as raw materials for the core layer, polyethylene and isotactic polypropylene are mixed, a vibration energy field is introduced, high-frequency vibration is used to promote the movement of molecular segments of the two polymers, and then a high-speed mixer is used to fully stir them;
[0026] S12: constructing an adhesive layer using ethylene vinyl acetate and an adhesive resin, mixing the ethylene vinyl acetate and the adhesive resin;
[0027] S13: The isolation layer is composed of polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, and the polyhedral oligomeric silsesquioxane and the nano zirconium oxide particles are mixed, and the mixing process adopts ultrasonic dispersion technology;
[0028] S14: The outer layer is composed of polyetheretherketone, ultraviolet absorber and slip agent, and these three materials are mixed;
[0029] S15: An ethoxylated amine antistatic agent is selected as a raw material for the antistatic layer, and the antistatic agent is dissolved in a solvent to prepare an antistatic coating solution, and then the antistatic coating solution is evenly coated on the outermost layer of the film using a coating technique. After the coating is completed, the film is dried to remove the solvent residue and solidify the antistatic layer.
[0030] In the method for preparing a multi-layer co-extruded PE stretch wrap film as described above, in S2, a multi-channel die is used, and the multi-channel die design allows the formation of a gradient layer structure, in which the composition gradually changes from one layer to another, thereby improving the compatibility between layers.
[0031] In the method for preparing a multi-layer co-extruded PE stretch wrap film as described above, in S3, air cascade cooling is combined with water cooling to achieve uniform cooling and reduce thermal stress, thereby obtaining better film performance.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] Nano zirconia has excellent wear resistance and high temperature resistance, while polyetheretherketone has good chemical resistance and mechanical strength. The wear resistance of nano zirconia is enhanced by the chemical resistance of polyetheretherketone, so that the film has wear resistance and high temperature resistance while maintaining high mechanical strength, which is suitable for packaging materials in high temperature environments.
[0034] The rigid core of polyhedral oligomeric silsesquioxane provides additional support for polyethylene, which significantly improves the mechanical properties of the composite material. This complementarity not only improves the mechanical properties of the composite material, but also improves the thermal properties through the nanostructure of polyhedral oligomeric silsesquioxane. At the same time, the uniform dispersion of polyhedral oligomeric silsesquioxane also avoids the performance degradation caused by agglomeration.
[0035] Polyethylene, as a matrix material, provides the membrane with flexibility and basic strength. The addition of polyhedral oligomeric silsesquioxane and nano-zirconia particles significantly improves the rigidity and hardness of the membrane through its nanoscale reinforcement effect. This synergistic effect allows the membrane to maintain flexibility while enhancing its ability to resist deformation and damage due to external forces.
[0036] Both POSS and nano-zirconia particles have excellent thermal stability. Their addition increases the thermal decomposition temperature of the PE matrix, allowing the membrane to maintain stable performance in high-temperature environments, making the membrane suitable for high-temperature application scenarios, such as food thermal processing, high-temperature logistics, etc.
[0037] The addition of ethylene-vinyl acetate (EVA) and adhesive resin enhances the bonding force between film layers and reduces the permeation channels of gas and liquid. At the same time, the nano effect of POSS and nano zirconium oxide particles further enhances the barrier properties of the film, making the film more effective in blocking external factors such as oxygen and moisture, thereby extending the shelf life of the packaged contents.
[0038] In general, the present invention not only improves the basic properties of the film (such as mechanical strength, thermal stability, etc.), but also gives the film specific functionality (such as barrier properties, weather resistance, chemical resistance, etc.). This enables the film to better meet the diverse application requirements and improves the comprehensive performance and market competitiveness of the product. At the same time, the compatibility between the components is good, ensuring the stability of the production process and the reliability of product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM photograph of the wrapping film of Example 4 of the present invention magnified 8000 times;
[0040] Figure 2 It is a data bar chart of the embodiments, control examples and comparative examples of the present invention. DETAILED DESCRIPTION
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0042] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0043] A multi-layer co-extruded PE stretch wrapping film comprises the following components in parts by weight: 50-70 parts of polyethylene, 1-5 parts of polyhedral oligomeric silsesquioxane, 5-15 parts of ethylene-vinyl acetate, 3-10 parts of adhesive resin, 5-15 parts of polypropylene, 1-3 parts of nano zirconium oxide particles, 1-5 parts of polyetheretherketone, 1-3 parts of antistatic agent, 0.5-2 parts of slip agent and 0.5-2 parts of ultraviolet absorber.
[0044] The molecular weight distribution index (MWD) of polyethylene is 3.0-3.5; the polyhedral oligomeric silsesquioxane is an octahedral structure, in which the silicon-oxygen bond is the main connecting bond, so as to improve the heat resistance and mechanical strength of the film; the VA content in ethylene-vinyl acetate is 20-25%; the mass fraction of polar groups in the adhesive resin is 1-3%, and the polar groups include carboxyl and hydroxyl groups, and the adhesive resin is one of rosin resin, terpene resin, phenolic resin and petroleum resin; the polypropylene is isotactic polypropylene, and its melt flow rate is 2-5g / 10min, so as to improve the tensile strength and heat resistance of the film; the crystal structure of polyetheretherketone is orthorhombic system; the particle size of nano zirconium oxide particles is 50-100nm; the antistatic agent is an ethoxylated amine antistatic agent, the slip agent is erucic acid amide, and the ultraviolet absorber is a benzophenone ultraviolet absorber.
[0045] It should be noted that polyethylene is a branched structure PE to enhance the toughness and tensile properties of the membrane; polyhedral oligomeric silsesquioxane has multiple reaction sites, which enables it to act as a "bridge" to connect multiple PE chains, build a more stable network structure, and improve the overall performance of the membrane.
[0046] Example
[0047] Material selection
[0048] Branched polyethylene (PE): Choose PE resin with a branched structure, which can effectively disperse stress during stretching and enhance the toughness and tensile properties of the film. Polyhedral oligomeric silsesquioxane (POSS): Choose POSS with multiple reaction sites, which can react chemically with PE chains to form stable chemical bonds, thereby building a more stable network structure.
[0049] Preparation process
[0050] Material mixing: Mix the branched PE resin with POSS. The mass ratio of PE resin to POSS can be 95:5. Ensure that both are evenly dispersed during the mixing process.
[0051] Melt coextrusion: The mixed materials are melt coextruded through multi-layer coextrusion technology. During the coextrusion process, the temperature, pressure and speed of each layer are precisely controlled to ensure that the reaction sites of the PE chain and POSS can be effectively combined.
[0052] Stretching and winding: The melt co-extruded film is stretched and wound to form a stretch film with excellent toughness and tensile properties.
[0053] Performance testing and data
[0054] Improved toughness: Compared with linear PE, branched PE can significantly improve the toughness of the film. Through testing, the elongation at break of the stretch film with branched PE can be increased by about 20% during the stretching process.
[0055] Improved tensile properties: Due to the synergistic effect of branched PE and POSS, the tensile strength of the wrapping film is significantly improved. Experimental data show that compared with the branched PE film without POSS, the tensile strength of the composite film with POSS added can be increased by about 15%.
[0056] Stability of network structure: Multiple reaction sites of POSS form stable chemical bonds with PE chains, building a more stable network structure. This structure enables the wrapping film to disperse stress more effectively when subjected to external forces, improving the durability and service life of the film. Through comparative experiments, the performance retention rate of the composite film with POSS added after repeated stretching is significantly higher than that of the film without POSS.
[0057] It should be noted that polyhedral oligomeric silsesquioxane has a hollow spherical structure, which can not only reduce weight, but also form micropores in the membrane, improving the air permeability and thermal insulation performance of the membrane; nano-zirconia has a one-dimensional nanostructure, including nanowires and nanorods, forming an effective reinforcement skeleton in the membrane, greatly improving the strength and rigidity of the membrane. The reinforcement skeleton efficiency index is set as RSEI, then:
[0058] RSEI=\frac{\ph i\t imesE_{ZrO_2}}{1-\ph i}
[0059] E_{ZrO_2} is the elastic modulus of nano-zirconia; \ph i is the volume fraction of nano-zirconia.
[0060] Assuming E_{ZrO_2}=200GPa;\ph i=0.1(the volume fraction of nano-zirconia is 10%), then: The RSEI value of 22.22 indicates a relatively high reinforcement efficiency, suggesting that the nano-zirconia particles are effectively enhancing the mechanical properties of the composites.
[0061] To achieve a hollow spherical structure of polyhedral oligomeric silsesquioxane (POSS) to improve air permeability and thermal insulation performance, and to utilize the one-dimensional nanostructure of nano zirconium oxide to enhance the strength and rigidity of the membrane, the following examples are used to specifically illustrate:
[0062] Material preparation
[0063] Polyhedral oligomeric silsesquioxane (POSS): Select POSS with a hollow spherical structure, and its particle size can be adjusted as needed within the range of 10-100 nanometers. Nanozirconia: Select nanozirconia with a one-dimensional nanostructure (such as nanowires and nanorods), with a diameter between 10-100 nanometers and a length that can be adjusted as needed. PE (polyethylene) resin: As a basic material, it is used to prepare multi-layer co-extruded stretch wrapping film.
[0064] Preparation steps
[0065] Mixing: Evenly mix POSS, nano-zirconia and PE resin in a high-speed mixer. The mixing can be carried out in a ratio of 5% of the total volume of POSS and 3% of the nano-zirconia.
[0066] Melt coextrusion: The mixed materials are melt coextruded through a multi-layer coextruder to form a PE film containing POSS and nano-zirconia. During the coextrusion process, the air permeability and thermal insulation properties of the film can be controlled by adjusting the ratio and thickness of each layer.
[0067] Stretching and winding: The melt co-extruded film is stretched and wound to form a winding film with certain tensile strength and toughness.
[0068] Performance testing and data
[0069] Weight reduction: Due to the addition of hollow spherical POSS, the density of the composite film is reduced compared with pure PE film, thereby reducing the weight. The density of pure PE film is 0.95g / cm 3 , while the density of the composite film after adding POSS was reduced to 0.90 g / cm 3 about.
[0070] Improved air permeability and thermal insulation performance: The hollow spherical structure of POSS forms micropores in the film, which improves the air permeability of the film. Compared with pure PE film, the air permeability of the composite film can be increased by about 30%. At the same time, these micropores also help to improve the thermal insulation performance of the film and reduce the efficiency of heat conduction.
[0071] Enhanced strength and rigidity: The one-dimensional nanostructure of nano zirconium oxide forms an effective reinforcement skeleton in the membrane. Compared with pure PE membrane, the tensile strength of the composite membrane can be increased by about 50%, and the flexural modulus (rigidity index) can be increased by about 40%.
[0072] Embodiment 1
[0073] A multi-layer co-extruded PE stretch wrap film comprises the following components in parts by weight: 50 parts of polyethylene (Sinopec), 1 part of polyhedral oligomeric silsesquioxane (Xuancheng Jingrui New Materials Co., Ltd.), 5 parts of ethylene vinyl acetate (Mitsubishi Chemical), 3 parts of adhesive resin (terpene resin, Guangdong Ketai New Materials Co., Ltd.), 5 parts of polypropylene (isotactic polypropylene, Sinopec), 1 part of nano zirconium oxide particles (Xuancheng Jingrui New Materials Co., Ltd.), 1 part of polyetheretherketone (Victrex), 1 part of antistatic agent (ethoxylated amine antistatic agent, Hai'an Petrochemical Plant, Jiangsu Province), 0.5 part of slip agent (erucic acid amide, Aksu PMC erucic acid amide, Guangzhou Chuanju Chemical Technology Co., Ltd.), and 0.5 part of ultraviolet absorber (benzophenone ultraviolet absorber, UV-9).
[0074] The embodiment also provides a method for preparing a multi-layer co-extruded PE stretch wrap film, comprising the following steps:
[0075] S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent;
[0076] S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are the outermost layers. Multi-layer co-extrusion equipment is used, and the extruder temperature settings are: core layer 180℃, adhesive layer 160℃, isolation layer 190℃, outer layer 280℃, antistatic layer 150℃. Ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer. The thickness ratio of each layer is: core layer 35%, adhesive layer 12%, isolation layer 23%, outer layer + antistatic layer 30% in total;
[0077] S3: solidify the multilayer melt by cooling in a water bath, the water temperature is controlled at 20°C, and the cooling time is 5 minutes;
[0078] S4: Biaxial stretching, firstly stretching in the machine direction by rollers with increasing speed, with an initial speed of 1 m / min, a final speed of 5 m / min, and a stretching ratio of 3 times, and then stretching using a tentering machine in the transverse direction, with a stretching temperature of 120°C and a stretching ratio of 3.5 times, controlling the temperature to achieve the desired stretching ratio and final properties, and then using a winder to obtain a multi-layer co-extruded PE stretch wrap film.
[0079] Embodiment 2
[0080] A multi-layer co-extruded PE stretch wrap film comprises the following components in parts by weight: 55 parts of polyethylene, 2 parts of polyhedral oligomeric silsesquioxane, 7 parts of ethylene-vinyl acetate, 4 parts of adhesive resin, 6 parts of polypropylene, 2 parts of nano zirconium oxide particles, 2 parts of polyetheretherketone, 2 parts of antistatic agent, 0.7 parts of slip agent (erucic acid amide), and 0.8 parts of ultraviolet absorber.
[0081] The embodiment also provides a method for preparing a multi-layer co-extruded PE stretch wrap film, comprising the following steps:
[0082] S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent;
[0083] S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are the outermost layers. Multi-layer co-extrusion equipment is used, and the extruder temperature settings are: core layer 185℃, adhesive layer 165℃, isolation layer 195℃, outer layer 285℃, antistatic layer 155℃. Ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer. The thickness ratio of each layer is: core layer 38%, adhesive layer 10%, isolation layer 22%, outer layer + antistatic layer 30% in total;
[0084] S3: The multilayer melt is solidified by cooling in a water bath, the water temperature is controlled at 22°C, and the cooling time is 6 minutes;
[0085] S4: Biaxial stretching, firstly stretching in the machine direction by rollers with increasing speed, with an initial speed of 1 m / min, a final speed of 6 m / min, and a stretching ratio of 4 times, and then stretching using a tentering machine in the transverse direction, with a stretching temperature of 125°C and a stretching ratio of 3.8 times. The temperature is controlled to achieve the desired stretching ratio and final properties, and then a winder is used to obtain a multilayer co-extruded PE stretch wrap film.
[0086] Embodiment 3
[0087] A multi-layer co-extruded PE stretch wrap film comprises the following components in parts by weight: 60 parts of polyethylene, 3 parts of polyhedral oligomeric silsesquioxane, 11 parts of ethylene-vinyl acetate, 7 parts of adhesive resin, 12 parts of polypropylene, 2 parts of nano zirconium oxide particles, 4 parts of polyetheretherketone, 2 parts of antistatic agent, 1.5 parts of slip agent (erucic acid amide), and 1.7 parts of ultraviolet absorber.
[0088] The embodiment also provides a method for preparing a multi-layer co-extruded PE stretch wrap film, comprising the following steps:
[0089] S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent;
[0090] S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are the outermost layers. Multi-layer co-extrusion equipment is used, and the extruder temperature settings are: core layer 190℃, adhesive layer 160-180℃, isolation layer 200℃, outer layer 290℃, antistatic layer 160℃. Ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer. The thickness ratio of each layer is: core layer 32%, adhesive layer 15%, isolation layer 25%, outer layer + antistatic layer 28% in total;
[0091] S3: solidify the multilayer melt by cooling in a water bath, the water temperature is controlled at 25°C, and the cooling time is 8 minutes;
[0092] S4: Biaxial stretching, firstly stretching in the machine direction by rollers with increasing speed, with an initial speed of 2m / min, a final speed of 7m / min, and a stretching ratio of 4 times, and then stretching using a tentering machine in the transverse direction, with a stretching temperature of 130°C and a stretching ratio of 4.2 times. The temperature is controlled to achieve the desired stretching ratio and final properties, and then a winder is used to obtain a multilayer co-extruded PE stretch wrap film.
[0093] Embodiment 4
[0094] A multi-layer co-extruded PE stretch wrap film comprises the following components in parts by weight: 70 parts of polyethylene, 5 parts of polyhedral oligomeric silsesquioxane, 15 parts of ethylene-vinyl acetate, 10 parts of adhesive resin, 15 parts of polypropylene, 3 parts of nano zirconium oxide particles, 5 parts of polyetheretherketone, 3 parts of antistatic agent, 2 parts of slip agent (erucic acid amide), and 2 parts of ultraviolet absorber.
[0095] The embodiment also provides a method for preparing a multi-layer co-extruded PE stretch wrap film, comprising the following steps:
[0096] S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent;
[0097] S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are the outermost layers. Multi-layer co-extrusion equipment is used, and the extruder temperature settings are: core layer 200℃, adhesive layer 180℃, isolation layer 210℃, outer layer 300℃, antistatic layer 170℃. Ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer. The thickness ratio of each layer is: core layer 32%, adhesive layer 13%, isolation layer 20%, outer layer + antistatic layer 35% in total;
[0098] S3: solidify the multilayer melt by cooling in a water bath, the water temperature is controlled at 30°C, and the cooling time is 10 minutes;
[0099] S4: Biaxial stretching, firstly stretching in the machine direction by rollers with increasing speed, with an initial speed of 2m / min, a final speed of 8m / min, and a stretching ratio of 5 times, and then stretching using a tentering machine in the transverse direction, with a stretching temperature of 140°C and a stretching ratio of 4.5 times. The temperature is controlled to achieve the desired stretching ratio and final properties, and then a winder is used to obtain a multilayer co-extruded PE stretch wrap film.
[0100] Comparative Example 1
[0101] A multi-layer co-extruded PE stretch wrapping film is basically the same as the fourth embodiment, except that: S1 specifically includes:
[0102] S11: Select polyethylene (PE) and isotactic polypropylene (iPP) with suitable melt index and molecular weight as raw materials for the core layer. These two materials have good mechanical properties and thermal stability, and are ideal for building the core layer. Mix PE and iPP to ensure that the core layer has uniform performance in the subsequent processing, introduce a vibration energy field, promote the movement of molecular segments of the two polymers through high-frequency vibration, enhance interfacial interaction, and achieve a more uniform mixing, and then use a high-speed mixer to fully stir, the stirring temperature is controlled at 170°C, and the stirring time lasts for 15 minutes to ensure that the materials are evenly mixed;
[0103] S12: Use ethylene vinyl acetate (EVA) and adhesive resin to construct the adhesive layer. EVA has good flexibility and adhesion, while the adhesive resin can further enhance the bonding strength between the layers. EVA and adhesive resin are mixed, and an appropriate amount of plasticizer can be added during the mixing process to improve the processing performance of the adhesive layer. The mixing temperature is controlled at 160°C and the mixing time is 10 minutes to ensure full fusion between the components;
[0104] S13: The isolation layer is composed of polyhedral oligomeric silsesquioxane (POSS) and nano zirconium oxide particles. These two materials have good barrier properties and thermal stability, and can effectively improve the barrier effect of the film. POSS and nano zirconium oxide particles are mixed, and an appropriate amount of dispersant is added to ensure uniform dispersion of the nanoparticles in the isolation layer. The mixing process uses ultrasonic dispersion technology, and the dispersion time lasts for 60 minutes to ensure sufficient dispersion of the nanoparticles and uniformity of the isolation layer;
[0105] S14: The outer layer is composed of polyetheretherketone (PEEK), UV absorber and slip agent. PEEK has excellent weather resistance and mechanical properties, UV absorber can improve the UV resistance of the film, and slip agent can improve the surface slipperiness of the film. These three materials are mixed, and an appropriate amount of antioxidant can be added during the mixing process to improve the aging resistance of the outer layer. The mixing temperature is controlled at 170°C and the mixing time is 15 minutes to ensure full fusion and uniform distribution of each component;
[0106] S15: An ethoxylated amine antistatic agent is selected as the raw material for the antistatic layer. This antistatic agent has excellent antistatic properties and stability, and can effectively prevent various problems caused by static electricity during the use of the film. The antistatic agent is dissolved in a suitable solvent according to a preset concentration (such as 1.5%) to prepare an antistatic coating solution. The antistatic coating solution is then evenly coated on the outermost layer of the film using a coating technique, and the coating thickness is controlled at 1.0 microns to ensure the uniformity and effectiveness of the antistatic layer. After coating, the film is dried to remove solvent residues and solidify the antistatic layer. The drying temperature is controlled at 100°C and the drying time lasts for 10 minutes.
[0107] Comparative Example 2
[0108] A multi-layer co-extruded PE stretch wrap film is basically the same as Example 4, except that: in S2, a multi-channel die is used to ensure accurate control of the thickness ratio of each layer, and the multi-channel die design allows the formation of a gradient layer structure in which the composition gradually changes from one layer to another, thereby improving the compatibility between layers.
[0109] Comparative Example 3
[0110] A multi-layer co-extruded PE stretch wrap film is basically the same as the fourth embodiment, except that: in S3, air cascade cooling is combined with water cooling to achieve uniform cooling and reduce thermal stress, thereby obtaining better film performance.
[0111] Comparative Example 1
[0112] A multi-layer co-extruded PE stretch wrap film is basically the same as the fourth embodiment, except that nano zirconium oxide particles are not added during the preparation process.
[0113] Comparative Example 2
[0114] A multi-layer co-extruded PE stretch wrap film is basically the same as the fourth embodiment, except that no polyetheretherketone is added during the preparation process.
[0115] Comparative Example 3
[0116] A multi-layer co-extruded PE stretch wrapping film is basically the same as the fourth embodiment, except that no polyhedral oligomeric silsesquioxane is added during the preparation process.
[0117] Comparative Example 4
[0118] A multi-layer co-extruded PE stretch wrap film is basically the same as the fourth embodiment, except that the transverse stretching process S4 is omitted in the preparation step.
[0119] The stretch films prepared in the above-mentioned Examples 1 to 4, Comparative Examples 1 to 3, and Comparative Examples 1 to 4 were tested:
[0120] Tensile properties test:
[0121] National standard: GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"
[0122] Testing method: Use a universal material testing machine to stretch the film at the rate specified in the standard, record the force change during the stretching process, and calculate the tensile strength and elongation at break.
[0123] Thermal stability test:
[0124] National Standard: GB / T 19466.3-2004 "Plastics Differential Thermal Analysis (DTA) Part 3: Determination of Melting and Crystallization Temperature and Thermal Enthalpy"
[0125] Detection method: Use differential thermal analyzer to measure the melting temperature and thermal enthalpy change of the membrane material and evaluate its thermal stability.
[0126] Barrier performance testing:
[0127] National standard: GB / T 1038-2000 "Plastic film and sheeting gas permeability test method pressure difference method"
[0128] Detection method: Use a gas permeability tester to measure the permeability of the membrane material to specific gases, such as oxygen, nitrogen, etc.
[0129] Wear resistance test:
[0130] National Standard: GB / T 1689-1998 "Determination of wear resistance of vulcanized rubber (using Akron abrasion machine)"
[0131] Test method: Although this standard is aimed at rubber, its method can also be used to test the wear resistance of plastic films, and the wear of the film material can be measured by an abrasion machine.
[0132] The results are shown in Table 1:
[0133] Table 1
[0134]
[0135] Through the above Table 1, it can be directly obtained that the tensile strength gradually increases from Example 1 to Example 4. The melting temperature fluctuates slightly in Examples 1 to 4, but remains stable overall. The melting temperature mainly reflects the thermal stability of the material, and the materials in these embodiments all show good thermal stability. In Examples 1 to 4, the oxygen permeability remains unchanged. This shows that in these embodiments, the barrier properties of the materials are very stable and are not affected by the component ratio and processing conditions. This is related to the uniform dispersion of polyhedral oligomeric silsesquioxane (POSS) and nano zirconium oxide particles in the isolation layer, which effectively improve the barrier properties of the film. The abrasion amount increases slightly in Examples 1 to 4, but the overall change is not large. This means that with the increase of certain components (such as polyethylene and nano zirconium oxide particles), the wear resistance of the film decreases slightly, but still remains within an acceptable range. The abrasion amount reflects the wear resistance of the material, and the materials in these embodiments all show good wear resistance.
[0136] In summary, after the stretch films prepared in Examples 1 to 4 were tested, the performance of various data was better.
[0137] Reference Figure 1-2 After the prepared stretch films were tested, the control example 1 showed the highest tensile strength, which was due to the fine processing and mixing of the components in S1, especially the enhancement of the interfacial interaction and the dispersibility of the nanoparticles through high-frequency vibration and ultrasonic dispersion technology. The control example 2, its multi-channel mold design improved the interlayer compatibility, thereby enhancing the tensile strength. The control example 3 is similar to the example 4, but slightly improved, because the optimization of the cooling process reduces the thermal stress.
[0138] The melting temperature of control example 1 is the highest, indicating that it has good thermal stability, which is related to the careful selection of raw materials and the optimization of the mixing process. The melting temperatures of control examples 2 and 3 are slightly increased, but the increase is smaller than that of control example 1.
[0139] The oxygen transmission rate of control example 1 is the lowest, showing that it has the best barrier performance, which is related to the uniform dispersion of nanoparticles in the isolation layer and the addition of POSS. The oxygen transmission rates of control examples 2 and 3 are also relatively low, indicating that the improvement of interlayer compatibility and the optimization of the cooling process are also helpful to improve the barrier performance.
[0140] The wear loss of control example 1 is the lowest, indicating that it has the best wear resistance, which is due to the fine mixing of the components and the uniform dispersion of the nanoparticles. The wear losses of control examples 2 and 3 are also relatively low, but slightly higher than that of control example 1.
[0141] In summary, by optimizing different steps in the preparation process, the three control examples all showed improvements over Example 4 in terms of tensile strength, melting temperature, oxygen permeability and abrasion loss. These improvements are attributed to the careful selection of raw materials, optimization of the mixing process, use of multi-channel molds and improvement of the cooling process.
[0142] In Example 4 and Comparative Example 1, where other conditions were the same, after the nano zirconium oxide particles were removed from Comparative Example 1, the tensile strength and melting temperature decreased, while the oxygen permeability and abrasion loss increased. This indicates that nano zirconium oxide plays an important role in improving the wear resistance of the film and maintaining high temperature stability.
[0143] After removing polyetheretherketone from comparative example 2, the tensile strength decreased and the abrasion loss increased, which indicates that polyetheretherketone plays an important role in improving the mechanical strength and abrasion resistance of the membrane.
[0144] After removing POSS from comparative example 3, the tensile strength and melting temperature decreased significantly, indicating that POSS plays an important role in enhancing the mechanical properties and thermal stability of the film. Its rigid core provides support for PE, thereby significantly improving the overall performance of the composite material.
[0145] After omitting the transverse stretching step in comparative example 4, the tensile strength and melting temperature dropped significantly, while the oxygen permeability and abrasion loss increased significantly. This shows that the biaxial stretching process is crucial to improving the comprehensive properties of the film, which helps to achieve a high stretch ratio of the film and optimize the final properties.
[0146] Nano-zirconia has excellent wear resistance and high temperature resistance, while polyetheretherketone has good chemical resistance and mechanical strength. The synergistic effect of the two can enhance the wear resistance and high temperature resistance of the film, while improving its chemical resistance and mechanical strength, making it suitable for high temperature environments and applications with high wear resistance requirements.
[0147] The wear resistance of nano-zirconia is enhanced by the chemical resistance of polyetheretherketone, so that the film has wear resistance and high temperature resistance while maintaining high mechanical strength, making it suitable for packaging materials in high temperature environments.
[0148] The rigid core of polyhedral oligomeric silsesquioxane (POSS) provides additional support for PE, significantly improving the mechanical properties of the composites.
[0149] The nanostructure of POSS also helps to improve the thermal stability of the composites.
[0150] The rigid core of POSS and the flexible segments of PE form a complementary relationship. This complementarity not only improves the mechanical properties of the composite material, but also improves the thermal properties through the nanostructure of POSS. At the same time, the uniform dispersion of POSS also avoids the performance degradation caused by agglomeration.
[0151] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A multi-layer co-extruded PE stretch wrap film, characterized in that: The invention comprises the following components in parts by weight: 50-70 parts of polyethylene, 1-5 parts of polyhedral oligomeric silsesquioxane, 5-15 parts of ethylene-vinyl acetate, 3-10 parts of adhesive resin, 5-15 parts of polypropylene, 1-3 parts of nano zirconium oxide particles, 1-5 parts of polyetheretherketone, 1-3 parts of antistatic agent, 0.5-2 parts of lubricant and 0.5-2 parts of ultraviolet absorber.
2. A multi-layer co-extruded PE stretch wrap film according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 53 parts of polyethylene, 4 parts of polyhedral oligomeric silsesquioxane, 8 parts of ethylene-vinyl acetate, 5 parts of adhesive resin, 9 parts of polypropylene, 2 parts of nano zirconium oxide particles, 3 parts of polyetheretherketone, 2 parts of antistatic agent, 0.8 parts of lubricant and 1.5 parts of ultraviolet absorber.
3. The multi-layer co-extruded PE stretch wrap film according to claim 1, characterized in that: The molecular weight distribution index of the polyethylene is 3.0-3.5; the polyhedral oligomeric silsesquioxane is an octahedral structure, in which the silicon-oxygen bond is the main connecting bond; the VA content in the ethylene-vinyl acetate is 20-25%; the mass fraction of the polar group in the adhesive resin is 1-3%, the polar group includes carboxyl and hydroxyl, and the adhesive resin is one of rosin resin, terpene resin, phenolic resin, and petroleum resin; the polypropylene is isotactic polypropylene, and its melt flow rate is 2-5g / 10min; the crystal structure of the polyetheretherketone is an orthorhombic system; the particle size of the nano zirconium oxide particles is 50-100nm; the antistatic agent is an ethoxylated amine antistatic agent, the lubricant is erucamide, and the ultraviolet absorber is a benzophenone ultraviolet absorber.
4. The multi-layer co-extruded PE stretch wrap film according to claim 1, characterized in that: The polyethylene is a branched structure PE; the polyhedral oligomeric silsesquioxane has multiple reaction sites, which enables it to connect multiple PE chains to build a more stable network structure.
5. The multi-layer co-extruded PE stretch wrap film according to claim 1, characterized in that: The polyhedral oligomeric silsesquioxane has a hollow spherical structure; the nano zirconium oxide has a one-dimensional nanostructure, including nanowires and nanorods, forming a reinforcement skeleton in the film, and setting the reinforcement skeleton efficiency index as RSEI, then: RSEI=\frac{\phi\timesE_{ZrO_2}}{1-\phi} E_{ZrO_2} is the elastic modulus of nano-zirconia; \phi is the volume fraction of nano-zirconia.
6. A method for preparing a multi-layer co-extruded PE stretch wrap film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: The core layer is constructed using polyethylene and isotactic polypropylene, the adhesive layer is constructed using ethylene-vinyl acetate and adhesive resin, the isolation layer includes polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, the outer layer includes polyetheretherketone, ultraviolet absorber, and lubricant, and the antistatic layer is an ethoxylated amine antistatic agent; S2: The core layer is in the middle, the adhesive layer surrounds the core layer, the isolation layer is on the outside, and the outer layer and antistatic layer are on the outermost layer. Multi-layer co-extrusion equipment is used to ensure that the extrusion rate of each extruder is synchronized to maintain the thickness ratio of each layer; S3: solidification of the multilayer melt by cooling in a water bath; S4: Biaxial stretching, first in the machine direction by increasing the speed of the roller stretching, and then in the transverse direction using a tenter stretching machine, and then using a winder, to obtain a multi-layer co-extruded PE stretch wrap film.
7. The method for preparing a multi-layer co-extruded PE stretch wrap film according to claim 6, characterized in that: Said S1 specifically includes: S11: polyethylene and isotactic polypropylene are selected as raw materials for the core layer, polyethylene and isotactic polypropylene are mixed, a vibration energy field is introduced, high-frequency vibration is used to promote the movement of molecular segments of the two polymers, and then a high-speed mixer is used to fully stir them; S12: constructing an adhesive layer using ethylene vinyl acetate and an adhesive resin, mixing the ethylene vinyl acetate and the adhesive resin; S13: The isolation layer is composed of polyhedral oligomeric silsesquioxane and nano zirconium oxide particles, and the polyhedral oligomeric silsesquioxane and the nano zirconium oxide particles are mixed, and the mixing process adopts ultrasonic dispersion technology; S14: The outer layer is composed of polyetheretherketone, ultraviolet absorber and slip agent, and these three materials are mixed; S15: An ethoxylated amine antistatic agent is selected as a raw material for the antistatic layer, and the antistatic agent is dissolved in a solvent to prepare an antistatic coating solution, and then the antistatic coating solution is evenly coated on the outermost layer of the film using a coating technique. After the coating is completed, the film is dried to remove the solvent residue and solidify the antistatic layer.
8. The method for preparing a multi-layer co-extruded PE stretch wrap film according to claim 6, characterized in that: In S2, a multi-channel mold is used. The multi-channel mold design allows the formation of a gradient layer structure in which the composition gradually changes from one layer to another, thereby improving the compatibility between the layers.
9. The method for preparing a multi-layer co-extruded PE stretch wrap film according to claim 6, characterized in that: In S3, air cascade cooling is combined with water cooling to achieve uniform cooling and reduce thermal stress, thereby obtaining better film performance.
Citation Information
Patent Citations
POSS (polyhedral oligomeric silsesquioxanes) modified high barrier three-layer co-extrusion packaging film and preparation method thereof
CN102019738A
Multi-layer composite membrane and preparation method thereof
CN108189499A
Composite film as well as preparation method and application thereof
CN109334192A
High-toughness wear-resistant polyphenylene sulfide composite material
CN110643179A
Laminated film
JP2005067012A
Cited By
Preparation process of multilayer polypropylene capacitor film
CN120863117A